A Design and Development of WebGIS Distribution System based on Smart Logistics - Hongbo Hao (Atlantis Press, 2021)
The vigorous development of the logistics industry provides a solid foundation for China’s economic prosperity. However, with the concept of “smart logistics” proposed, the transformation of the logistics industry to information technology presents great challenges. Aiming at the transportation problem in logistics industry, based on the analysis of the research status at home and abroad, this paper designs a balanced/unbalanced transportation problem solving method based on Monte Carlo similarity and genetic algorithm. In this paper, Monte Carlo similarity method is introduced to design and develop a WebGIS transportation and distribution system based on genetic algorithm. This paper analyzes the information requirements, functional requirements and performance requirements of the transportation and distribution system and gives the overall architecture of the system. The system designs the database table relations and table in detail. Finally, the running test results show that the system can effectively reduce the distribution cost, increase enterprise profits and improve enterprise efficiency.